Metodología integral para el control del agua en fondo en un campo de crudo pesado de la Cuenca de los Llanos Orientales (2019)
The oil and gas industry is highly related to water production, companies produce in average three barrels for every single barrel of petroleum and spend more than 40 thousand millions of dollars annually (Bailey et al., 2000). The case of Frontera Energy is not different and the current water cut for most of their fields is above 95%; resulting in an oil-water relationship of 1 to21. Problem that increases with a water drive mechanism and an adverse mobility ratio. The objective of this work is to propose a methodology to control the downhole water production of three selected wells, through the analysis of reservoir properties and production data. A review of the geological conditions was made, the production of the field was analyzed, three critical wells were selected in terms of their water production, the mechanisms of water production in each of these wells were diagnosed, the behavior of the BSW was predicted in the future and a decision matrix was executed to know which is the most appropriate intervention. Likewise, an Excel Macro was developed (MICAF), which collects all these steps and makes each analysis more effective.